PEMANFAATAN MEDIA SOSIAL YOUTUBE HUMAS DPRD KOTA SURAKARTA DALAM MEMBANGUN CITRA KOMISI IV DI MASYARAKATANALISIS PEMBERITAAN KEGIATAN SIDAK KOMISI IV DPRD KOTA SURAKARTA PADA UNGGAHAN YOUTUBE OLEH HUMAS DALAM MEMBANGUN CITRA POSITIF - Oktifiana Nurliya Ikasari; Rahmad Wisudawanto; Hasbullah Aziz (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2025)
The upload of inspection activity videos by Commission IV on the @DPRDKotaSurakarta YouTube account has not fully provided transparent information to the public. This can be seen from the video uploads that do not yet fulfill the completeness elements of 5W+1H. Therefore, this research aims to analyze the news coverage of Commission IV's inspection activities posted on YouTube by the public relations office in building a positive image. This research is qualitative and uses primary data sources from YouTube uploads and questionnaires as secondary data sources. The primary data source in this study consists of uploaded videos. This research uses John Fiske's (1990) content analysis model, which reveals that 40 out of 65 uploaded videos of Commission IV's inspection activities have met the 5W+1H news elements. Thus, Commission IV has provided transparent information to the public. To understand the positive image of Commission IV, Sutisna's (2001) image theory was used, leading to the finding that the news videos can build a positive image for Commission IV. This is supported by questionnaire results showing that more than 60% of respondents agree that the video uploads of Commission IV's inspection activities help the public understand the expectations of the Public Relations Office of DPRD Kota Surakarta, comprehend the expectations of Commission IV DPRD Kota Surakarta, facilitate effective communication, influence public perception, reflect positive public expectations and perceptions towards Commission IV, and have a significant and positive impact on Commission IV DPRD Kota Surakarta.